A multi-agent system to help Farmville players on game management tasks - Neves, Romina (2019)
Nowadays social networks are used for various recreational purposes. It is believed that every day is spent on average two hours per user in these networks games. Farmville is an application relating to one of the most successful social networks: Facebook. Farmville is a game that allows each user to use a diverse set of actions available for managing a virtual farm. However, this management quickly becomes a boring and time consuming process and often the user quits the application. In this context this project main objective is the development of a multi-agent system able to assist the player in Farmville. The system will help the user in most of his management tasks on the farm. The use of the implemented system ensures greater progress in the game, because there is a decrease in the time spent in performing the tasks enabling the user to focus on the strategies for advancing in the game.